2021
DOI: 10.1093/gerona/glab368
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Hand Sensory Function and Force Control in Older Adults: Are Current Hand Assessment Tools Enough?

Abstract: Background The ability to grasp and manipulate objects is essential for performing activities of daily living. However, there is limited information regarding age-related behavioral differences in hand sensorimotor function due, in part, to the lack of assessment tools capable of measuring subtle but important differences in hand function. The purpose of this study was to demonstrate performance differences in submaximal force control and tactile pattern recognition in healthy older adults us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Since TPD was correlated to most force tracking performance variables across all three phases of force tracking, group force tracking performance differences likely are related in part to age-related sensation degradation. Previous studies have found decline in performance with TPD and SWMT with aging (Kaneko et al 2005 ; Logue et al 2022 ). Although there were no group differences with SWMT, TPD has been found to correlate with object identification (Novak et al 1993a , b ) and predicts performance for tasks that require sustained pinch grip, more so than the SWMT (Dellon and Kallman 1983 ).…”
Section: Discussionmentioning
confidence: 87%
“…Since TPD was correlated to most force tracking performance variables across all three phases of force tracking, group force tracking performance differences likely are related in part to age-related sensation degradation. Previous studies have found decline in performance with TPD and SWMT with aging (Kaneko et al 2005 ; Logue et al 2022 ). Although there were no group differences with SWMT, TPD has been found to correlate with object identification (Novak et al 1993a , b ) and predicts performance for tasks that require sustained pinch grip, more so than the SWMT (Dellon and Kallman 1983 ).…”
Section: Discussionmentioning
confidence: 87%
“…More sensitive and specific tests are needed to evaluate the functional impact of motor decline in PWH. 39,40 Dysfunction in other components of motor function such as muscle strength, coordination, and gait (which were not evaluated in this analysis) have also been observed in the context of HIV [41][42][43] ; future studies are required to identify whether IDO activation is associated with deficits across the spectrum of motor functioning in HIV. IDO activation is strongly associated to aging and chronic inflammatory conditions such as osteoporosis, and independently predicts mortality in PWH on ART.…”
Section: Discussionmentioning
confidence: 99%